Hollywood Leadership Theory, Part 1 - Christopher Barrick (Academic Chairpersons Conference Proceedings, 2022)
Leadership advice is readily available in journals and books, but are those sources most relevant for today’s leaders? This presentation aims to take a different approach by presenting sound leadership principles as seen in television and movies, translating Hollywood leadership to the everyday life of academic departments.
Keywords: leadership; chairs; media; television; film